Faculty Senate Recommendation to the Provost, May 5, 2016 - Salisbury University Faculty Senate (My University, 2016)
A recommendation from the Faculty Senate to the Provost on the distribution of Faculty merit pay.
Keywords: Shared Governance; Governance Consortium